EKSPLORASI ETNOMATEMATIKA KONSEP POLA BILANGAN DALAM PERMAINAN TRADISIONAL - Ramadhina, Anisa Laela; Septiana, Citra; Pebrianti, Melinda; Wahidin, Wahidin (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2021)
This study aims to study the relationship between mathematics and culture in Indonesia, one of which is the traditional game of Nasi Goreng Kecap and Mejikuhibiniu. This research is considered important because it teaches students to see real-world activities clearly by being integrated into mathematical ideas. This research uses an ethnographic approach and a library study (literature study) which is a type of qualitative research. The result of this research is that the traditional game Nasi Goreng Kecap and Mejikuhibiniu contains the concept of number patterns, which can be developed in a learning design for number pattern material so that it can change the student's paradigm that mathematics is still considered abstract science to be more fun mathematics